The use of distance technologies in Rural Education in the context of the development of a system for assessing the quality of teaching - Iryna Sadova; Oleksandr Balanutsa; Iryna Vialkova; Oksana Voroshchuk; Halyna Lemko (Universidade Federal do Norte do Tocantins, 2022)
The main purpose of the article is to study the main qualities of the use of distance technologies in rural education in the context of COVID-19 in the context of the development of a system for assessing the quality of teaching. Distance and blended learning technologies have become familiar to the rural education system during the years of the coronavirus pandemic. The State Service for the quality of teaching in different countries has also adapted the tools for conducting institutional audits to the conditions of remote work or partially remote work. Adaptation requires the organization of rural educational activities so that institutions continue to work efficiently and effectively both in full-time and online learning. All components of the system of the educational process of rural education should also be changed, including finding new ways to assess the quality of teaching.